Complications Linked to Acute COVID-19 Phase during its Second Wave Era - Entesar Omran; Zenab Elfzzani; Amina Bshaena (AlQalam Journal of Medical and Applied Sciences, 2024)
Numerous global studies have documented the multi-systemic complications associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, there is a scarcity of research exploring SARS-CoV-2-related complications in Libya, specifically in Zawia city. Therefore, this study aimed to screen and identify complications of acute COVID-19 in 176 SARS-CoV-2 infected patients in Zawia city, Libya. As part of a past retrospective cohort study, 176 randomly selected volunteers who tested positive for SARS-CoV-2 between December 1, 2020, and February 28, 2021, in Zawia city participated in this research. Participants completed a questionnaire designed for COVID-19 patients, and the collected data were analyzed to achieve the objectives of this study. In the current study, we found that 73.9% of the COVID-19 patients were mild to moderate cases, while 26.1% were severe cases. Moreover, our recent research revealed that 90.9% of the COVID-19 patients experienced complications during the acute phase of the disease. The reported complications during this phase included psychological disorders (90%), pneumonia (35.6%), brain fog (19.4%), multi-joint pain (18.8%), hearing deficit (8.1%), acute respiratory failure (5.6%), acute cardiac injury (3.8%), thrombotic lesions (1.9%), and vision impairment (1.9%). Overall, our findings indicate that most of COVID-19 participants had mild to moderate disease, with approximately one quarter experiencing severe illness. Furthermore, the vast majority of patients had complications during the acute COVID-19 phase, with psychological disorders being the most commonly reported, followed by pneumonia. While rare, fatal complications such as acute respiratory failure, acute cardiac injury, and thrombotic lesions were observed in some participants. عدة دراسات أجريت حول العالم قد أفادت بالمضاعفات المتعددة المرتبطة بفيروس سارس-كوف-2 المسبب لمتلازمة الضيق التنفسي الحاد. ومع ذلك، هناك قلة في الأبحاث التي تستكشف المضاعفات المرتبطة بفيروس سارس-كوف-2 في ليبيا، وتحديداً في مدينة الزاوية. لذا، تهدف هذه الدراسة إلى فحص وتحديد مضاعفات كوفيد-19 الحاد في 176 مريضًا مصابًا بفيروس سارس-كوف-2 في مدينة الزاوية في ليبيا. كجزء من دراسة الاسترجاعية السابقة، شارك في هذا البحث 176 متطوعًا تم اختيارهم عشوائيًا وتبينت إصابتهم بفيروس سارس-كوف-2 بين الأول من ديسمبر 2020 و28 فبراير 2021 في مدينة الزاوية. أكمل المشاركون استبيانًا مصممًا لمرضى كوفيد-19، وتم تحليل البيانات المجمعة لتحقيق أهداف هذه الدراسة. في الدراسة الحالية، اكتشفنا أن 73.9% من مرضى كوفيد-19 كانوا حالات خفيفة إلى متوسطة، بينما كانت 26.1% حالات شديدة. علاوة على ذلك، أوضح البحت الحالي أن 90.9% من مرضى كوفيد-19 تعرضوا لمضاعفات خلال المرحلة الحادة للمرض. والمضاعفات المبلغ عنها خلال هذه المرحلة تشمل الاضطرابات النفسية (90%)، الالتهاب الرئوي (35.6%)، الضبابية الدماغية (19.4%)، ألم في العديد من المفاصل (18.8%)، نقص السمع (8.1%)، الفشل التنفسي الحاد (5.6%)، الإصابة القلبية الحادة (3.8%)،تجلط الأوعية الدموية (1.9%)، وضعف الرؤية (1.9%). بشكل عام، تشير نتائجنا إلى أن معظم مرضى الكوفيد-19 المشاركين في هذه الدراسة كانت لديهم حالة خفيفة إلى متوسطة، و حوالي ربع المرضى عانوامن مرضً شديدً. علاوة على ذلك، كان لدى غالبية المرضى مضاعفات خلال المرحلة الحادة للكوفيد-19 ، حيث كانت الاضطرابات النفسية هي الأكثر شيوعًا، يليها الالتهاب الرئوي. و لقد تم ملاحظة مضاعفات قاتلة على الرغم من ندرتها في بعض المشاركين مثل الفشل التنفسي الحاد، الإصابة القلبية الحادة، وتجلط الأوعية الدموية .من الضروري إجراء دراسات بحثية موسعة في مدينة الزاوية لتحديد النطاق الكامل للمضاعفات المرتبطة بالمرحلة الحادة للكوفيد-19. ستوفر مثل هذه الدراسات نصائح قيمة تعزز فهمنا لتأثير الفيروس على الأفراد